2015
DOI: 10.1111/acer.12914
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation in Alcohol Dependence

Abstract: These findings clarify the specific pattern of emotion dysregulation associated with alcohol dependence. They also suggest that (1) abstinence is associated with a shift toward more adaptive emotion regulation patterns and that (2) inefficient regulation strategies may lead to craving and the maintenance of alcohol use. If these findings are confirmed through longitudinal and mediation designs, they will have important clinical implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 48 publications
6
51
0
2
Order By: Relevance
“…For example, in a study in which both depressed patients and nondepressed controls were instructed to use likely maladaptive ER strategies (such as rumination or suppression) in response to experimentally induced dysphoric mood states, depressed individuals utilized maladaptive strategies more often than nondepressed controls and had more difficulties overcoming these states than nonclinical individuals (Campbell‐Sills et al., ; Liverant, Brown, Barlow, & Roemer, ). Similar findings have been reported for eating disorders (Mills, Newman, Cossar, & Murray, ), substance disorders (Berking et al., ; Petit et al., ), somatoform disorders (Remmel, ), and psychotic disorders (Strauss et al., ).…”
Section: Introductionsupporting
confidence: 79%
“…For example, in a study in which both depressed patients and nondepressed controls were instructed to use likely maladaptive ER strategies (such as rumination or suppression) in response to experimentally induced dysphoric mood states, depressed individuals utilized maladaptive strategies more often than nondepressed controls and had more difficulties overcoming these states than nonclinical individuals (Campbell‐Sills et al., ; Liverant, Brown, Barlow, & Roemer, ). Similar findings have been reported for eating disorders (Mills, Newman, Cossar, & Murray, ), substance disorders (Berking et al., ; Petit et al., ), somatoform disorders (Remmel, ), and psychotic disorders (Strauss et al., ).…”
Section: Introductionsupporting
confidence: 79%
“…EDR is conceptualized as one of the core components of SUDs [56,57]. EDR is a possible mechanism underlying the indirect relationship between negative affectivity and greater alcohol and drug misuse [68,69], alcoholrelated problems [71], craving for alcohol [62,70] and the maintenance of alcohol use [62]. Previous studies suggest that the period of early abstinence is particularly related with EDR [61,64].…”
Section: Discussionmentioning
confidence: 99%
“…Emotion regulation refers to the modulation of emotional arousal, the awareness, understanding, and acceptance of emotions, as well as the ability to act in desired ways regardless of emotional state [59]. In recent years, increasing attention has been given to EDR as a potentially common feature of many forms of addiction [55], including chemical addictions such as alcohol [57,[60][61][62], marijuana [63], cocaine [64], and illicit substance use in the past 30 days [65]. Some researchers have argued that individuals who have EDR are more likely to engage in addictive behaviours in an attempt to escape from, or minimize, negative moods and/or try alleviate distressing feelings [66].…”
mentioning
confidence: 99%
“…Previous research has shown that individuals with alcohol dependence may utilize alcohol as a means by which to regulate unpleasant emotional states, such as stress. Specifically, inefficient emotion regulation strategies have been related to increased craving for alcohol (of which desire for alcohol is a facet; Petit et al, ). In order to combat the high levels of alcohol use observed in Type D individuals, it may be useful to target their stress levels and foster improved coping, social and emotion regulation skills.…”
Section: Discussionmentioning
confidence: 99%